2021
DOI: 10.1080/19420862.2021.1963094
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted proteomics reveals upregulation of stress response pathways during CHO-based monoclonal antibody manufacturing process leading to disulfide bond reduction

Abstract: Monoclonal antibody (mAb) interchain disulfide bond reduction can cause a loss of function and negatively impact the therapeutic’s efficacy and safety. Disulfide bond reduction has been observed at various stages during the manufacturing process, including processing of the harvested material. The factors and mechanisms driving this phenomenon are not fully understood. In this study, we examined the host cell proteome as a potential factor affecting the susceptibility of a mAb to disulfide bond reduction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In the MATLAB environment, all features were dimensionally reduced to principal components (PCs), and each run was mapped to the PC space. Due to the condition‐specific behavior of cell culture and batch variation (Park et al, 2021), it was reasonable to evaluate the anomaly of samples within one culture condition. However, Hotelling's T 2 , which evaluates all samples at once regardless of culture condition, was not suitable for our condition‐specific data sets.…”
Section: Methodsmentioning
confidence: 99%
“…In the MATLAB environment, all features were dimensionally reduced to principal components (PCs), and each run was mapped to the PC space. Due to the condition‐specific behavior of cell culture and batch variation (Park et al, 2021), it was reasonable to evaluate the anomaly of samples within one culture condition. However, Hotelling's T 2 , which evaluates all samples at once regardless of culture condition, was not suitable for our condition‐specific data sets.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, similar trends in mAb reduction were observed at all culture scales when the culture medium and process conditions were the same for all of them. Even when the same cell line was used, however, mAb reduction varied among culture scales when their culture media and process parameters differed (Cura et al 2020;Handlogten et al 2020;Park et al 2021). Here, we observed that mAb reduction trends also varied with culture medium composition (data not shown).…”
Section: Factor Determining Antibody Reductionmentioning
confidence: 99%
“…This poses challenges in product purification due to the potential risks related to immunogenicity and regulatory compliance 6–9 . Some residual HCPs, for example, reductase and lipase, may also deteriorate the antibody quality or degrade the formulation components 10–14 . Therefore, it is critical to terminate the cell culture before extensive cell lysis to ensure product quality.…”
Section: Introductionmentioning
confidence: 99%